The peninsular Malaysia flooding - a spatio-temporal analysis of precipitation records - Nurul Afzan, Musa Hasni (2014)
Floods are regular natural disaster that frequently occurs in Peninsular Malaysia, which happens every year during the monsoon season. Especially second inter monsoon (October) to early North-East monsoon (November - December). During North-East monsoon, wind brings heavy rainfall to Peninsular Malaysia, which often results in flooding. The main study objective is to analysis spatial-temporal of precipitation records during flooding. The specific objectives of the study are as follow; to produce spatialtemporal rainfall distribution maps and to assess the depth, duration and intensity of the rainfall that can cause flooding. This study uses TMPA satellite-based rainfall, to map the spatial-temporal distribution of rainfall during flood events for period 2000-2013. From the maps, the assessment to identify the depth, duration and intensity of the rainfall that can cause flooding were performed. The results show that, the flooding occurs due to the variability of depth, duration and intensity of rainfall. However, at particular places the flooding that occurred at different periods, experiencing rainfall with the same intensity. In conclusion, floods can happen at a place with different rainfall characteristics (i.e. depth, duration, intensity). In addition, flooding able reoccurred at the same place with the same rainfall intensity.